Predictors and outcomes of stroke mimics in patients treated with intravenous thrombolysis: a single-center retrospective cohort study - Klimbytė, Brigita; Matijošaitis, Vaidas; Vaitkus, Antanas (Frontiers in Neurology, 2025)
BackgroundIntravenous thrombolysis (IVT) is most effective in acute ischemic stroke (AIS) when administered promptly; however, efforts to reduce treatment times may increase the risk of treating stroke mimics (SM). This retrospective single-center study aimed to determine the prevalence of SM among patients treated with IVT, compare them with AIS cases, evaluate the clinical implications of IVT administration, and identify possible predictors of SM.MethodsPatients who received IVT for suspected AIS between January 2022 and December 2024 were retrospectively analyzed. Only patients without early ischemic changes on non-contrast CT and without intracranial occlusion on CT angiography were included. Based on clinical presentation, imaging, and discharge diagnosis, patients were classified as AIS or SM. Data collected included demographics, clinical features, risk factors, treatment times, NIHSS scores, mRS scores, and post-IVT complications.ResultsOf 724 patients treated with IVT, 330 met the inclusion criteria. Among them, 293 (88.8%) had confirmed AIS and 37 (11.2%) were SM. SM patients were significantly younger (mean age 57.4 vs. 70.2 years, p < 0.001), had fewer vascular risk factors, and higher rates of migraine, epilepsy, and vestibular disorders. Sensory symptoms and headache were more common in SM, whereas motor symptoms and aphasia were more frequent in AIS. Although initial NIHSS scores were comparable, SM demonstrated greater improvement at 1 and 24 h post-IVT. Functional outcomes were better in SM, with 92% achieving a discharge mRS of 0 compared to 19% in AIS (p < 0.001). No intracranial hemorrhage or seizures were observed in the SM group. LASSO selection and Firth’s bias-reduced logistic regression analysis identified younger age, presence of sensory symptoms, history of migraine or epilepsy, and absence of atrial fibrillation as independent predictors of SM.ConclusionStroke mimics accounted for 11.2% of cases treated with intravenous thrombolysis and differed significantly from AIS in clinical and demographic characteristics. IVT was safe in SM, with no major complications observed. Several clinical predictors may aid in early differentiation. However, these findings should be interpreted cautiously due to the limited number of mimic cases.